ASSESSING THE PERFORMANCE OF COOPERATIVE BANKS IN THE PHILIPPINES: A DATA ENVELOPMENT ANALYSIS - Dante R. Garcia; Maria Luisa P. Mirasol (International Journal of Accounting, Finance and Business, 2020)
This paper assesses the performance of cooperative banks (CBs) in the Philippines for the period 2015-2018 by calculating their technical efficiencies. Slack-based data envelopment analysis (SBM-DEA) was applied in a dataset of 23 CBs provided by Bangko Sentral ng Pilipinas. Adopting the intermediation approach, total deposits and fixed assets were used as input variables and total loans and other earning assets were used as output variables. Results showed that three CBs were efficiently strong having operated at their most productive scale size (MPSS), seven CBs were efficiently weak, six were inefficient (without slacks), and seven were inefficient (with slacks). On the average, the overall technical efficiency is 64.1% implying that CBs need to reduce their inputs by 35.9% while producing the same amount of outputs. The sources of inefficiency were identified to be both from poor management of inputs and inappropriate scale of operations. The CBs should improve management competencies and practice rightsizing to achieve optimal scale of operations.